Mixed nitrogen forms enhance growth and photosynthetic nitrogen use efficiency by optimizing nitrogen metabolism and leaf N allocation in Gisela 6 cherry rootstock - Xu, Xinxiang; Tang, Yan; He, Liu; Sun, Yanxia; Liu, Daliang; Wang, Yuxia; Li, Fangdong; Zhao, Lingling; Song, Laiqing; Wang, Fen; Li, Yanju; Zhang, Xu (Frontiers in Plant Science, 2025)
Nitrogen (N) is the most important nutrient for plant growth and development. However, the mechanisms by which the form and supply of N regulate the growth and N utilization of cherry rootstock are unclear at present. We investigated the effects of different N supply levels and N forms on the growth, N uptake, assimilation and distribution, and photosynthetic N use efficiency (PNUE) of Gisela 6 cherry rootstock seedlings. The results showed that a high N level and a single supply of either nitrate N or ammonium N hindered N uptake and assimilation, increased photosynthetic limitation, reduced PNUE and 15N use efficiency, and inhibited cherry rootstock growth. Further experiments showed that a mixed supply of nitrate N and ammonium N maintained high transcription levels of nitrate and ammonium transporters as well as N metabolism enzyme activities, thereby increasing the net inflow rates of NO3− and NH4+ into roots and the soluble protein content of leaves. In addition, a mixed N supply reduced oxidative damage to leaves by maintaining an appropriate nitrate/ammonium ratio, increased the proportion of leaf N allocated to photosynthetic N, decreased leaf cell wall thickness, and enhanced stomatal conductance, mesophyll conductance, and the maximum carboxylation efficiency. This resulted in reduced leaf photosynthetic limitation, increased leaf net photosynthetic rate and PNUE, and ultimately enhanced the growth of Gisela 6 cherry rootstock seedlings. Our results provide a basis for optimizing N management strategies in cherry cultivation.